The preserving effect of social protection on social cohesion during the COVID-19 pandemic: Evidence from Kenya - Christoph Strupat (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
This paper examines empirically whether social protection in the form of adapted social assistance programmes are affecting social cohesion during the COVID-19 pandemic. Using unique primary data from nationally representative, in-person surveys from Kenya allows for the exploration of the effect of social protection on attributes of social cohesion (trust, cooperation and identity). The analysis employs a difference-in-differences approach that compares households with and without social assistance coverage before and after the first wave of the pandemic. The findings suggest that social assistance can have a positive effect on attributes of social cohesion, but only in regions that faced larger restrictions due to lockdown policies. Turning to the analysis without focusing on lockdown regions, social assistance does not affect attributes of social cohesion. Overall, the results suggest that only under specific circumstances existing national social assistance programmes and their adaptation in times of large covariate shocks, such as the COVID-19 pandemic, can be beneficial for social cohesion.
Keywords: 330; social protection; social assistance; social cohesion; COVID-19; Kenya